(untitled) (Research, Society and Development, 2022)
Clinical case report of a patient who suffered ischemic stroke (CVA) after abuse of lysergic acid diethylamide (LSD), presenting disinhibition syndrome. A 43-year-old male patient, without comorbidities, but with a history of severe drug addiction, presented a sudden neurological deficit after LSD abuse. Evolved with severe headache, followed by syncope. Upon awakening, he presented a deviation of the labial rhyme to the right and left hemiparesis. Cranial computed tomography ruled out bleeding, hypodensity, or cerebral edema. A stroke was hypothesized and thrombolysis with Alteplase was performed 1 hour after the onset of symptoms. The patient was transferred to the intensive care unit, where there was a picture of sequelae in the frontal region, manifested as disinhibition syndrome, establishing inappropriate and depraved verbal contact, with erotization of sexual disinhibition. Family members reported that the patient had an unrecognizable personality, compared to before the brain event. Behavioral syndromes caused by stroke are rare, thus, the follow-up of this case was relevant, since in addition to not finding another case of stroke caused by LSD abuse in the literature, the emergence of disinhibition syndrome was verified as a symptomatic manifestation.